FORMATION OF PROFESSIONAL COMPETENCIES IN THE COURSE OF PREPARING AND CONDUCTING BUSINESS GAMES IN ENGLISH CLASSES - Jabbarova, Anora (Журнал иностранных языков и лингвистики, 2020)
THIS ARTICLE IS ABOUT FORMATION OF PROFESSIONAL COMPETENCIES IN THE COURSE OF PREPARING AND CONDUCTING BUSINESS GAMES IN ENGLISH CLASSES